A Discourse Analysis of American Folktale âthe Monkeyâs Pawâ - Syam, Andi Tenrisanna (Universitas Ahmad Dahlan, 2017)
Discourse analysis studies language in use taking into account important elements such as coherence (unity of the text) and cohesion (tools that tie together sentences, e.g. pronouns). American folktale âthe monkeyâs pawâ is written by W.W. Jacobs.